Implikasi Pengawasan Otoritas Jasa Keuangan (OJK) dalam Meningkatkan Kepercayaan Nasabah pada Produk dan Layanan Bank Syariah (Studi Kasus di Bank Syariah Indonesia (BSI) KC Bukittinggi) - Aulia Safitri; Nini Sumarni (Lembaga Yasin AlSys, 2026)
The implications of supervision by the Financial Services Authority (OJK) for customer trust in Islamic banking have become a focus in various previous studies; however, research that specifically discusses the relationship between OJK supervisory mechanisms and the formation of customer trust at the branch operational level remains limited. This study aims to analyze the implications of OJK supervision in increasing customer trust in the products and services of Bank Syariah Indonesia (BSI), Bukittinggi Branch Office. This study employed a qualitative approach with a case study design. The research participants were BSI customers selected through the purposive sampling technique. Data were collected through semi-structured interviews, observation, and documentation and were then analyzed using thematic analysis. The results show that OJK supervision through regulation, control, and consumer protection contributes to creating a sense of security and increasing customer trust. However, customers’ understanding of supervisory mechanisms remains relatively limited, so trust is also influenced by service experience, interpersonal relationships, and ease of use of digital services, particularly among younger age groups. These findings contribute to the development of institutional theory and trust theory by showing that institutional legitimacy can shape trust even though customers do not have an in-depth understanding of supervisory mechanisms. The conclusion of the study emphasizes the importance of strengthening transparency and financial literacy in increasing customer trust. The practical implication is that banking institutions and regulators need to optimize public communication strategies so that the role of OJK supervision can be more widely understood by Islamic banking customers.